Learn Intergation from Davneet Sir - Live lectures starting soon!

Examples

Example 1

Example 2

Example 3

Example 4 Important

Example 5

Example 6 Important

Example 7

Example 8 Important

Example 9

Example 10

Example 11 Important

Example 12 Important

Example 13 Important

Example 14 Important

Example 15 Deleted for CBSE Board 2023 Exams

Example 16 Deleted for CBSE Board 2023 Exams

Example 17 Deleted for CBSE Board 2023 Exams

Example 18 Important Deleted for CBSE Board 2023 Exams

Example 19 Important Deleted for CBSE Board 2023 Exams

Example 20 Deleted for CBSE Board 2023 Exams

Example 21 Deleted for CBSE Board 2023 Exams

Example 22 Deleted for CBSE Board 2023 Exams

Example 23 Important Deleted for CBSE Board 2023 Exams You are here

Example 24 Deleted for CBSE Board 2023 Exams

Example 25 Important Deleted for CBSE Board 2023 Exams

Example 26 Deleted for CBSE Board 2023 Exams

Example 27 Important Deleted for CBSE Board 2023 Exams

Example 28 (a) Deleted for CBSE Board 2023 Exams

Example 28 (b)

Example 28 (c)

Example 29 Deleted for CBSE Board 2023 Exams

Example 30 Deleted for CBSE Board 2023 Exams

Example 31 Important Deleted for CBSE Board 2023 Exams

Example 32 Deleted for CBSE Board 2023 Exams

Example 33 Deleted for CBSE Board 2023 Exams

Example 34 Deleted for CBSE Board 2023 Exams

Example 35 Deleted for CBSE Board 2023 Exams

Example 36 Deleted for CBSE Board 2023 Exams

Example 37 Important Deleted for CBSE Board 2023 Exams

Example 38 Deleted for CBSE Board 2023 Exams

Example 39 Deleted for CBSE Board 2023 Exams

Example 40 Deleted for CBSE Board 2023 Exams

Example 41

Example 42 Important

Example 43 Important

Example 44

Example 45 (a) Deleted for CBSE Board 2023 Exams

Example 45 (b) Deleted for CBSE Board 2023 Exams

Example 46 Important

Example 47 Important

Example 48 Important

Example 49

Example 50

Example 51 Important

Chapter 1 Class 12 Relation and Functions

Serial order wise

Last updated at Jan. 28, 2020 by Teachoo

Example 23 (Method 1) Let f : N → Y be a function defined as f (x) = 4x + 3, where, Y = {y ∈ N: y = 4x + 3 for some x ∈ N}. Show that f is invertible. Find the inverse. Checking inverse Step 1 f(x) = 4x + 3 Let f(x) = y y = 4x + 3 y – 3 = 4x 4x = y – 3 x = (𝑦 − 3)/4 Rough Checking inverse of f:X → Y Step 1: Calculate g: Y → X Step 2: Prove gof = IX Step 3: Prove fog = IY g is the inverse of f Let g(y) = (𝑦 − 3)/4 where g: Y → N Step 2: gof = g(f(x)) = g(4x + 3) = ((4𝑥 + 3) − 3)/4 = (4𝑥 + 3 − 3)/4 = 4𝑥/4 = x = IN Rough Checking inverse of f:X → Y Step 1: Calculate g: Y → X Step 2: Prove gof = IX Step 3: Prove fog = IY g is the inverse of f Step 3: fog = f(g(y)) = f((𝑦 − 3)/4) = 4 ((𝑦 − 3)/4) + 3 = y – 3 + 3 = y + 0 = y = IY Since gof = IN and fog = IY, f is invertible & Inverse of f = g(y) = (𝒚 − 𝟑)/𝟒 Rough Checking inverse of f:X → Y Step 1: Calculate g: Y → X Step 2: Prove gof = IX Step 3: Prove fog = IY g is the inverse of f Example 23 (Method 2) Let f : N → Y be a function defined as f (x) = 4x + 3, where, Y = {y ∈ N: y = 4x + 3 for some x ∈ N}. Show that f is invertible. Find the inverse. f is invertible if f is one-one and onto Checking one-one f(x1) = 4x1 + 3 f(x2) = 4x2 + 3 Putting f(x1) = f(x2) 4x1 + 3 = 4x2 + 3 4x1 = 4x2 x1 = x2 Rough One-one Steps: 1. Calculate f(x1) 2. Calculate f(x2) 3. Putting f(x1) = f(x2) we have to prove x1 = x2 If f(x1) = f(x2) , then x1 = x2 ∴ f is one-one Checking onto f(x) = 4x + 3 Let f(x) = y, where y ∈ Y y = 4x + 3 y – 3 = 4x 4x = y – 3 x = (𝑦 − 3)/4 Now, Checking for y = f(x) Putting value of x in f(x) f(x) = f((𝑦 − 3)/4) = 4((𝑦 − 3)/4) + 3 = y − 3 + 3 = y For every y in Y = {y ∈ N: y = 4x + 3 for some x ∈ N}. There is a value of x which is a natural number such that f(x) = y Thus, f is onto Since f is one-one and onto f is invertible Finding inverse Inverse of x = 𝑓^(−1) (𝑦) = (𝑦 − 3)/4 ∴ Inverse of f = g(y) = (𝒚 − 𝟑)/𝟒 where g: Y → N